Hubungan Self-compassion dengan Resiliensi pada Remaja dengan Orang Tua Bercerai - Laalah, Eunike Euangeline Trifena; Rahayu, Maria Nugraheni Mardi (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2024)
Divorce or termination of the relationship between husband and wife is one of the conflicts that can occur in the family and impact children. Adolescents with divorced parents can experience various problems, such as loneliness and anxiety, so self-compassion and resilience are needed to be able to rise. This study aims to see the relationship between self-compassion and resilience in late adolescents with divorced parents. This research method is quantitative, using Spearman's rho test design with linearity. The participants of this study were 200 late adolescents with divorced parents, and the sampling technique used was snowball sampling. The research scale used is the Self Compassion Scale (SCS) and the Resilience Scale (RS). This study found that there was a significant positive relationship between self-compassion and resilience in late adolescents with divorced parents (r = 0.250 with a sig. value of 0.000). Thus, the results obtained show that self-compassion has a relationship with resilience. Therefore, it is hoped that late adolescents with divorced people can have an increase in self-compassion and resilience within themselves.